1999
DOI: 10.1046/j.1365-2036.1999.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical economics review: medical management of inflammatory bowel disease

Abstract: Inflammatory bowel diseases, although they are uncommon and rarely fatal, typically present during the period of economically productive adult life. Patients may require extensive therapeutic intervention as a result of the chronic, relapsing nature of the diseases. Their medical management includes oral and topical 5-amino salicylic acid derivatives and corticosteroids, as well as antibiotics and immunosuppressive therapies. Assessing the cost-effectiveness of rival treatments requires valid, reliable global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…This finding is consistent with the view that decreased economic productivity contributes significantly to the overall societal costs of Crohn's disease since the illness develops during patients peak employment years. 10 Our results are also consistent with the work of Blomqvist and Ekbom 13 who found that Swedish patients with IBD retired an average of 14 years prior to the mandatory age of retirement. This observation is consistent with our finding of high unemployment rates in all age groups in this study.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding is consistent with the view that decreased economic productivity contributes significantly to the overall societal costs of Crohn's disease since the illness develops during patients peak employment years. 10 Our results are also consistent with the work of Blomqvist and Ekbom 13 who found that Swedish patients with IBD retired an average of 14 years prior to the mandatory age of retirement. This observation is consistent with our finding of high unemployment rates in all age groups in this study.…”
Section: Discussionsupporting
confidence: 95%
“…[1][2][3][4][5] As a result, Crohn's disease causes important disability and economic loss to patients and society. [6][7][8][9][10][11][12] Although inflammatory bowel disease (IBD) has been shown to result in a high cost to society, most analyses have likely underestimated the cost of IBD, since, for the most part, only direct costs have been considered. Indirect costs due to Crohn's disease are likely considerable.…”
mentioning
confidence: 99%
“…IBD is characterized by recurrent episodes and delayed healing, with its clinical manifestations of abdominal pain and diarrhea containing mucus, pus, and blood. The use of antibiotics and probiotics has been shown to be clinically effective for the treatment of IBD, in addition to traditional drug treatments such as amino salicylic acid drugs, corticosteroids, and immunosuppressive agents [26,27]. Traditional Chinese medicine has long been used in the treatment of IBD, because of its efficacy and lack of side effects [28][29][30].…”
Section: Original Papersmentioning
confidence: 99%
“…cure mediche, e in alcuni casi chirurgiche, e sono complessivamente un rilevante onere economico per il Sistema Sanitario Nazionale (SSN) e per la società [5].…”
Section: Farmeconomia E Percorsi Terapeutici 2003; 4 (4): 201-216unclassified